HOW TO MAKE ISLAMIC LAW AS THE STATE LEGAL POLICY OF INDONESIA: Constitutional and Sociological Arguments - Hapsin, Abu (Faculty of Shariah and Law, State Islamic University (UIN) Walisongo, 2017)
This article aims to answer some questions: what is the meaning of â€œequal rightâ€ and â€œreligious freedomâ€ written in the text of UUD 45? How if, in the name of religious freedom, other peopleâ€™s rights are offended? how if, in implementing Islamic law, others peopleâ€™s rights are offended? Indonesian Constitution (UUD 45) gives freedom to every follower of a given religion to concretize his religious convictions in public life provided that, in doing so, the fundamental right of others are not offended. The UUD 45 also gives freedom to every citizen to make his religious convictions or religious teachings become a state legal policy as long as he or she follows the procedural constitution written in the UUD 45. However, after becoming state legal policy, Islamic law can no longer be claimed â€œIslamic Lawâ€, because itâ€™s now provided for answering the partial question of life, namely how to administer the state. From a sociological point of view, in order that the process of legislation runs smoothly, Islamic Law should first be transformed into living norms. Hence, it will be easier for the society to abide the law which originated from living norms. Since the function of law in maintaining public peace and order depends, for its effectiveness, on the actual social norms of the community, social acceptance is of great importance. Two ways of resolution will be discussed in this article, these are democratic resolution and transforming Islamic Law into social norms.[]Artikel ini bertujuan untuk menjawab beberapa pertanyaan, apa arti